Improvement of the timing properties of Ce-doped oxyorthosilicate LYSO scintillating crystals. (April 2020) - Tamulaitis, G.; Auffray, E.; Gola, A.; Korzhik, M.; Mazzi, A.; Mechinski, V.; Nargelas, S.; Talochka, Y.; Vaitkevičius, A.; Vasil'ev, A.
Abstract: The aim of this work has been to improve the time resolution of radiation detectors for future high-energy physics experiments and medical imaging applications. Ce-doped oxyorthosilicate Lu2 SiO5 :Ce (LSO) and mixed oxyorthosilicate Lu1.6 Y0.4 SiO5 :Ce (LYSO) have been investigated as prospective scintillators for such high-time-resolution applications. A differential optical absorption technique with sub-picosecond time resolution upon selective excitation of Ce 3+ ions to different excited states has been adopted to study carrier dynamics in these scintillators, and coincidence time resolution measured using 511 keV γ-quanta has been exploited to test their timing properties. A delay in population of the emitting level of Ce 3+ has been observed, and is interpreted in terms of electron trapping, which is more pronounced in mixed yttrium-containing LYSO crystals due to composition fluctuations. It is shown that the delay, which affects the luminescence response time, can be eliminated by co-doping of LYSO:Ce with calcium at concentrations as low as 5 ppm. The faster kinetics of electron transfer correlates with a better coincidence time resolution. Thermalization and spatial distribution of non-equilibrium carriers has been studied theoretically to link the results obtained by the time-resolved differential optical absorption technique with the behavior of the non-equilibrium carriers generated by irradiation. Highlights: The time resolution of LYSO is more affected by carrier trapping than that of LSO. Carrier trapping in LYSO is enhanced by fluctuations in the compound composition. Ca-co-doping, even at a concentration of 5 ppm, improves the response time of LYSO:Ce. Femtosecond pump-probe spectroscopy is a useful tool for improving Ce-doped scintillators.